NILAI-NILAI PANCASILA DALAM FIKIH MEDIA SOSIAL - Ayun, Qurrota; Islamy, Athoillah (KOMUNIKASIA: Journal of Islamic Communication and Broadcasting, 2021)
This study aims to explore and identify the dimensions of Pancasila values ​​contained in the construction of the MUI Fatwa related to the General Guidelines for Bermuamalah in Social Media. This qualitative research is a literature study with a normative philosophical approach. The theory used as a theoretical framework, namely the philosophical values ​​of Pancasila. The results of the study conclude that there is a philosophical dimension of Pancasila values ​​in the construction of the MUI Fatwa regarding general guidelines for muamalah in social media. First, the value of the second precept in the first general guideline is in the form of awareness of the importance of realizing human social values ​​in social interactions on social media. Second, the values ​​of the first and second precepts in the second general guideline are in the form of the importance of making religious and state norms the basis of ethics in social interaction on social media. Third, the value of the fourth and fifth precepts in the third general guideline is an awareness to be careful in responding and disseminating information on social media and upholding the values ​​of equal rights and laws for social media users.